Evidence of active subglacial lakes under a slowly moving coastal region of the Antarctic Ice Sheet - J. F. Arthur; C. Shackleton; G. Moholdt; K. Matsuoka; J. van Oostveen (The Cryosphere)
Active subglacial lakes beneath the Antarctic Ice Sheet provide insights into the dynamic subglacial environment, with implications for ice-sheet dynamics and mass balance. Most previously identified lakes have been found upstream (>100 km) of fast-flowing glaciers in West Antarctica, and none have been found in the coastal region of Dronning Maud Land (DML) in East Antarctica. The regional distribution and extent of lakes as well as their timescales and mechanisms of filling–draining activity remain poorly understood. We present local ice surface elevation changes in the coastal DML region that we interpret as unique evidence of seven active subglacial lakes located under slowly moving ice near the grounding line margin. Laser altimetry data from ICESat-2 and ICESat (Ice, Cloud, and Land Elevation Satellites) combined with multi-temporal Reference Digital Elevation Model of Antarctica (REMA) strips reveal that these lakes actively fill and drain over periods of several years. Stochastic analyses of subglacial water routing together with visible surface lineations on ice shelves indicate that these lakes discharge meltwater across the grounding line. Two lakes are within 15 km of the grounding line, while another three are within 54 km. Ice flows 17–172 m a−1 near these lakes, much slower than the mean ice flow speed near other active lakes within 100 km of the grounding line (303 m a−1). Our results improve knowledge of subglacial meltwater dynamics and evolution in this region of East Antarctica and provide new observational data to refine subglacial hydrological models.